Walking With Horizontal Head Turns Is Impaired in Persons With Early-Stage Multiple Sclerosis Showing Normal Locomotion - Carpinella, Ilaria; Gervasoni, Elisa; Anastasi, Denise; Di Giovanni, Rachele; Tacchino, Andrea; Brichetto, Giampaolo; Confalonieri, Paolo; Solaro, Claudio; Rovaris, Marco; Ferrarin, Maurizio; Cattaneo, Davide (Frontiers in Neurology, 2022)
Background: Turning the head while walking (an action often required during daily-living) is particularly challenging to maintain balance. It can therefore potentially reveal subtle impairments in early-stage people with Multiple Sclerosis who still show normal locomotion (NW-PwMS). This would help in identifying those subjects who can benefit from early preventive exercise aimed at slowing the MS-related functional decline. Objectives: To analyze if the assessment of walking with horizontal head turns (WHHT) through inertial sensors is able to discriminate between healthy subjects (HS) and NW-PwMS and between NW-PwMS sub-groups. To assess if the discriminant ability of the instrumented WHHT is higher compared to clinical scores. To assess the concurrent validity of the sensor-based metrics. Methods: In this multicenter study, 40 healthy subjects (HS) and 59 NW-PwMS (Expanded Disability Status Scale (EDSS) ≤2.5, disease duration ≤5 years) were tested. Participants executed Item-6 of the Fullerton Advanced Balance scale–short (FAB-s) wearing three inertial sensors on trunk and ankles. The item required to horizontally turn the head at a metronome’s beat (100 bpm) while walking. Sensors’ signals were processed to compute spatio-temporal, regularity, symmetry, dynamic stability, and trunk sway metrics descriptive of WHHT. Results: Medio-lateral regularity, antero-posterior symmetry, and medio-lateral stability were reduced in NW-PwMS versus HS (p≤0.001), and showed moderate discriminant ability (area under the receiver operator characteristic curve [AUC]: 0.71-0.73). AP symmetry and ML stability were reduced (p≤0.026) in EDSS:2-2.5 versus EDSS:0-1.5 subgroup (AUC: 0.69-0.70). The number of NW-PwMS showing at least one abnormal instrumented metric (68%) was larger (p≤0.002) than the number of participants showing abnormal FAB-s-Item6 (32%) and FAB-s clinical scores (39%). EDSS:2-2.5 subgroup included more individuals showing abnormal instrumented metrics (86%) compared to EDSS:0-1.5 subgroup (57%). The instrumented metrics significantly correlated with FAB-s-Item6 and FAB-s scores (|Spearman’s rs|≥0.37, p<0.001), thus demonstrating their concurrent validity. Conclusions: The instrumented assessment of WHHT provided valid objective metrics that discriminated, with higher sensitivity than clinical scores, between HS and NW-PwMS and between EDSS subgroups. The method is a promising tool to complement clinical evaluation, and reveal subclinical impairments in persons who can benefit from early preventive rehabilitative interventions.